The Use of The Application “HSK Exam –汉语水平考试” In The HSK 4 Preparation Course of The Chinese Language Education Study Program 2022 Malang State University - Deva Arma Laresa; Aiga Ventivani; Deddy Kurniawan (Journal of Chinese Language and Culture Studies, 2025)
This research on the use of the “HSK EXAM-汉语水平考试” application in the HSK 4 Preparation course aims to understand the usage activities of the “HSK EXAM-汉语水平考试” application within the HSK 4 Preparation Course and students’ response to this application in the HSK 4 Preparation Course of the Mandarin Language Education Program 2022. The descriptive qualitative approach is the type of the research used in this study, utilizing the data analysis framework developed by Miles dan Huberman. The study acknowledges that the application received positive feedback from students. Mandarin language learners find the application very useful as it provides various HSK question sets and vocabulary. The research findings indicate that the application has the potential to be effective supplementary tool for the HSK 4 Preparation Course and offers valuable insights for the future development of technology-based Mandarin language teaching methods.